FAKTOR YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS MATARAMAN TAHUN 2021 - Novianty Novianty; Vonny Khresna Dewi; Rusmilawaty Rusmilawaty (MMJ (Mahakam Midwifery Journal), 2022)
Abstract Exclusive breastfeeding coverage at Mataraman Health Center in 2017 was 121 babies (23.18%) who received exclusive breastfeeding from 522 babies. In 2018, 46 babies (8.7%) received exclusive breastfeeding from 526 babies. In 2019, 136 babies (40.7%) were exclusively breastfeeding from 532 babies. Factors causing failure in exclusive breastfeeding by knowledge, belief, self-efficacy of mothers, and family support. The purpose of study was to determine the relationship of knowledge, belief, self-efficacy and family support of mothers with giving exclusive breastfeeding in the working area of Mataraman Health Center in 2021. This research method used analytic survey design using cross sectional. The population in study was all mothers who had babies aged >6-12 months and took samples using 76 samples of saturated results. The results of statistical tests showed that there was no relationship between knowledge (p = 0.269) and exclusive breastfeeding, and there was a relationship between belief (p = 0.035), self-efficacy (p = 0.030), and family support (husband) (p = 0.048) with breastfeeding exclusive. The conclusion of this study was that there was no relationship between knowledge and exclusive breastfeeding. There was a relationship of belief, self-efficacy, and family support (husband) with exclusive breastfeeding. Keywords: Exclusive breastfeeding, knowledge, belief, self-efficacy of mothers, and family support. Abstrak Cakupan ASI eksklusif di Puskesmas Mataraman pada tahun 2017 sebanyak 121 bayi (23,18%) yang mendapat ASI ekslusif dari 522 bayi. Pada tahun 2018 sebanyak 46 bayi (8,7%) yang mendapat ASI ekslusif dari 526 bayi. Pada tahun 2019 sebanyak 136 bayi (40,7%) yang mendapat ASI eksklusif dari 532 bayi. Faktor penyebab kegagalan dalam pemberian ASI eksklusif dipengaruhi oleh pengetahuan, kepercayaan, efikasi diri dan dukungan keluarga. Tujuan penelitian adalah untuk mengetahui hubungan antara pengetahuan, kepercayaan, efikasi diri ibu dan dukungan keluarga dengan pemberian ASI Eksklusif di wilayah kerja Puskesmas Mataraman Tahun 2021. Metode penelitian ini menggunakan rancangan survei analitik dengan pendekatan cross sectional. Populasi dalam penelitian seluruh ibu yang memiliki bayi usia >6-12 bulan dan pengambilan sampel menggunakan teknik Purposive Sampling berjumlah 76 orang. Analisa data menggunakan uji Chi-Square dengan α=0,05. Hasil uji statistik menunjukkan tidak ada hubungan pengetahuan (p = 0,269) dengan pemberian ASI eksklusif, serta ada hubungan kepercayaan (p = 0,035), efikasi diri (p = 0,030),dan dukungan keluarga (suami) (p = 0,048) dengan pemberian ASI eksklusif. Kesimpulan penelitian yaitu tidak ada hubungan pengetahuan dengan pemberian ASI eksklusif. Ada hubungan kepercayaan, efikasi diri, dan dukungan keluarga (suami) dengan pemberian ASI eksklusif. Kata kunci : Pemberian ASI Eksklusif, pengetahuan, kepercayaan, efikasi diri ibu, dan dukungan keluarga.